2019
DOI: 10.1051/e3sconf/201910504009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Socio-Economic Impacts of Zeolite Mining to Regional Development – Case Study

Abstract: The presented article deals with the impact of mining of mineral resources, namely zeolites, to the socio -economic area of regional development. Case study is focused on analysis of macroeconomic parameters of selected indicators for the implementation of the zeolite mining project in the Prešov region. This way we can point out to benefits for the state and the region. In accordance with the applicable legislation are quantified revenues for the municipality (or region) -the form of payments for the mining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In a previous Slovak study, it was also confirmed that the economic value of a deposit and of extraction in the form of income was not the only contribution for the region and the state but there was an added value in the form of raised social level and improved quality of life for the inhabitants. Created jobs improve the purchasing power of the region and increase trade and services [2]. Suggested model of management of RM exploitation in regional development with the goal to decrease interregional disparities and to increase the competitiveness of Slovakian regions with the tendency of increasing polarization in the region of Bratislava, had been constructed by the way that it could integrate following areas of analyzed problem solving, based on the studied cases in SR and worldwide:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous Slovak study, it was also confirmed that the economic value of a deposit and of extraction in the form of income was not the only contribution for the region and the state but there was an added value in the form of raised social level and improved quality of life for the inhabitants. Created jobs improve the purchasing power of the region and increase trade and services [2]. Suggested model of management of RM exploitation in regional development with the goal to decrease interregional disparities and to increase the competitiveness of Slovakian regions with the tendency of increasing polarization in the region of Bratislava, had been constructed by the way that it could integrate following areas of analyzed problem solving, based on the studied cases in SR and worldwide:…”
Section: Discussionmentioning
confidence: 99%
“…The exploitation of raw material (RM) determines the sustainable development of the Slovak Republic (SR) in the primary, secondary, and tertiary spheres as it affects the environmental quality and social and economic development [1,2]. Mining of RM deposits decreases the environmental quality [3,4] and, at the same time, affects the social and economic area of sustainable development [5,6] as the exploitation determines the creation of jobs [7,8], the level of payments for mining space, and extracted minerals [9,10], state budget revenues from the payment of taxes on dependent activities, taxes on corporate income, and in the form of VAT [11].…”
Section: Introductionmentioning
confidence: 99%